Cradle-to-Grave Environmental Sustainability of Railway Sleepers by Means of Life Cycle Assessment (LCA) Methodology: A Critical Review - Mohammad Siahkouhi; Maria Rashidi; Farah Firoozi; Sakdirat Kaewunruen; Guoqing Jing; Ruizhe Zhang (Circular Economy and Sustainability, 2026)
Railway sleepers are one of the main components of the railway tracks. This paper provides a comparison of cradle-to-grave environmental sustainability of different types of railway sleepers, including steel, timber, concrete, recycled plastic and fiber composite sleepers, and their environmental consequences. Interest in constructing railway tracks has been increased, many countries are extending their railway network worldwide. Therefore, there is a gap in comparison of newly suggested railway sleepers to the market such as recycled plastic sleepers considering environmental impacts during manufacturing, transportation, application, and disposal process. This review also presents environmental aspects of using each abovementioned sleeper type in case of CO 2 emission and recycling opportunities. This research can provide guidelines for industry adoption of different types of railway sleepers compared based on ISO 14040 and identical functional unit for life cycle management and analysis. The main challenge facing sleepers remains manufacturing process, especially, concrete, and composite sleepers, in energy consumption and CO 2 emission which causes environmental impacts. However, inconsistencies in data quality, functional unit definitions, and system boundaries limit comparability across studies. Most research focuses narrowly on carbon footprint, with limited attention to broader environmental indicators such as water use and toxicity. This review underscores the need for standardized LCA practices and region-specific inventory data to improve reliability and support sustainable decision-making in railway infrastructure planning and procurement.

Enhanced digital twins (EDTs) approach based on advanced inspection and technology adoption to achieve sustainable construction processes - Alaa O. Shehata; Ehsan Noroozinejad Farsangi; Gregory M. Morrison; Maria Rashidi; T.Y. Yang; Mohamed M. Mirdan (Energy and Buildings, 2025)

Mobility perceptions regarding the COVID-19 pandemic from around the world - Kiran Shakeel; Kasun Wijayaratna; Diego Maria Barbieri; Baowen Lou; Taha Hossein Rashidi (Travel Behaviour and Society, 2023)